2020
DOI: 10.1101/gr.253211.119
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and specific roles of cohesin STAG subunits in chromatin looping and transcriptional control

Abstract: Cohesin is a ring-shaped multiprotein complex that is crucial for 3D genome organization and transcriptional regulation during differentiation and development. It also confers sister chromatid cohesion and facilitates DNA damage repair. Besides its core subunits SMC3, SMC1A, and RAD21, cohesin in somatic cells contains one of two orthologous STAG subunits, STAG1 or STAG2. How these variable subunits affect the function of the cohesin complex is still unclear. STAG1-and STAG2-cohesin were initially proposed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 66 publications
(105 reference statements)
11
49
0
Order By: Relevance
“…Our results demonstrate that STAG1 and STAG2 display nearly identical distributions across the genome, despite not interacting together in a stable complex. Our finding that the STAG proteins do not physically interact corroborates similar coIP and microscopy results in mESCs and human colorectal cancer lines, and is consistent with a model where cohesin functions as a single ring, rather than as a pair of rings [8,23,25,27,32,41,42]. Several recent reports have found that STAG1 and STAG2 localize at many shared sites, but also localize to a subset of sites exclusively [23][24][25]27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results demonstrate that STAG1 and STAG2 display nearly identical distributions across the genome, despite not interacting together in a stable complex. Our finding that the STAG proteins do not physically interact corroborates similar coIP and microscopy results in mESCs and human colorectal cancer lines, and is consistent with a model where cohesin functions as a single ring, rather than as a pair of rings [8,23,25,27,32,41,42]. Several recent reports have found that STAG1 and STAG2 localize at many shared sites, but also localize to a subset of sites exclusively [23][24][25]27].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the STAG proteins do not physically interact corroborates similar coIP and microscopy results in mESCs and human colorectal cancer lines, and is consistent with a model where cohesin functions as a single ring, rather than as a pair of rings [8,23,25,27,32,41,42]. Several recent reports have found that STAG1 and STAG2 localize at many shared sites, but also localize to a subset of sites exclusively [23][24][25]27]. However, our analysis in mESCs does not identify a class of sites preferentially occupied by one specific cohesin-STAG complex, and agree with a recent report that shared sites reflect a population average, where some cells have cohesin-STAG1 and others have cohesin-STAG2 at an individual site [25].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We used our previously published ChIP-seq data from two biological replicates of adult mice livers for three proteins that form the cohesin complex: RAD21, STAG1 and STAG2 [55]. RAD21 is necessary for the formation of the core ring of the cohesin complex, which is completed with either STAG1 or STAG2 [56,57]. We defined colocalised events as those where at least two cohesin subunits overlap with CTCF binding.…”
Section: Recently Evolved Tissue-shared Ctcf Binding Efficiently Recrmentioning
confidence: 99%